1998
DOI: 10.1042/cs0940149
|View full text |Cite
|
Sign up to set email alerts
|

An Early Prenatal Exposure to Excess Glucocorticoid Leads to Hypertensive Offspring in Sheep

Abstract: 1. Recent studies in animals have linked fetal exposure to excess maternal glucocorticoids with the later occurrence of cardiovascular disorders, particularly hypertension. 2. To test the hypothesis that prenatal treatment could impact on adult blood pressure two groups of pregnant ewes were transported from the farm to the Institute at either 22-29 days of pregnancy (pretreatment group 1) or 59-66 days of pregnancy (pretreatment group 2), subjected to 48 h treatment with dexamethasone (0.28 mg day-1 kg-1 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
248
3
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(264 citation statements)
references
References 24 publications
9
248
3
4
Order By: Relevance
“…However, that exposure resulted in fetal glucocorticoid levels that were similar to those induced by the stress of premature delivery and RDS and were much lower than those resulting from the administration of glucocorticoids to prevent or treat neonatal chronic lung disease. 1 In contrast, the many animal studies that demonstrated that prenatal glucocorticoid exposure programmed postnatal blood pressure involved exposure either very early in gestation 4 or in high doses for long periods. 3 Unfortunately, there are no studies on animals of short-term, lower-dose exposure, comparable to that used in clinical practice.…”
Section: E376mentioning
confidence: 94%
See 1 more Smart Citation
“…However, that exposure resulted in fetal glucocorticoid levels that were similar to those induced by the stress of premature delivery and RDS and were much lower than those resulting from the administration of glucocorticoids to prevent or treat neonatal chronic lung disease. 1 In contrast, the many animal studies that demonstrated that prenatal glucocorticoid exposure programmed postnatal blood pressure involved exposure either very early in gestation 4 or in high doses for long periods. 3 Unfortunately, there are no studies on animals of short-term, lower-dose exposure, comparable to that used in clinical practice.…”
Section: E376mentioning
confidence: 94%
“…3 In a number of animal models, exposure to glucocorticoids before birth results in increased blood pressure in the offspring. 3,4 To date, the data on subsequent blood pressure among human subjects exposed prenatally to glucocorticoids for prevention of RDS have been contradictory. One nonrandomized cohort study found that extremely premature neonates exposed prenatally to glucocorticoids had higher blood pressure in the first 48 hours after birth.…”
mentioning
confidence: 99%
“…17,25 Although GCs are necessary for normal development, excess exposure has deleterious consequences for fetal growth and in animal models leads to the development of permanent hypertension, hyperglycemia, and hyperinsulinemia. 16,[26][27][28] Whether the dose and timing of exposure with prenatal betamethasone is sufficient to induce long-term programming changes remains unknown, but must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This overexposure is thought to occur via reduced activity of placental 11b-hydroxysteroid dehydrogenase, which acts to convert maternal glucocorticoids to inactive forms, or by increased activity of the glucocorticoid receptor in fetal tissues. Studies of rodents and sheep have demonstrated that exposure to synthetic glucocorticoids can impact on renal development and subsequent blood pressure (93)(94)(95)(96)(97) . The similarities in phenotype associated with dietary and glucocorticoid exposures have led to suggestions that they may act through a shared mechanism, i.e.…”
Section: Mechanisms Of Developmental Programmingmentioning
confidence: 99%
“…the pancreas and kidney) continues into postnatal life. (95) and rats at 15-16 d of gestation (97) . Although representing very different stages of gestation in sheep and rats, these time points are similar in terms of the stage of renal development, when increased apoptosis of mesenchymal cells could affect nephron formation and thus final glomerular number (137) .…”
Section: Disadvantages Of Working With Small-animal Modelsmentioning
confidence: 99%